Climate sensitivity of tree growth decreases with site humidity for a tropical tree species - Sophie A. Zwartsenberg; Frank J. Sterck; Iftakharul Alam; Niels P.R. Anten; Lucas A. Cernusak; Xenia Davide; Ingo Heinrich; Roosje Kemmink; José A. Medina-Vega; Sebastian Ramirez; Pieter A. Zuidema (Agricultural and Forest Meteorology, 2026)

Enhanced cesium removal from clay minerals using surfactant-assisted capacitive deionization - Jiaxin Hu; Sebastian Gonzalez Ramirez; Huagui Zhang; Jae.W. Lee; Timothy N. Hunter; David Harbottle (Chemical Engineering Journal, 2026)

Easy formation of AuPt nanoalloys on chitosan films and their synergistic effects in the catalyzed reduction of p-nitrophenol and hydrolysis of ammonia-borane - Oscar Ramirez; Gabriel Abarca; Nayara Mejías; Ángel Leiva; César Saldías; David Díaz Díaz; Sebastian Bonardd (Journal of Environmental Chemical Engineering, 2025)

Optimized CO2 photoreduction using cuprous oxide (Cu2O) nanoparticles synthesized using Psidium guajava extract - S. Torres-Arellano; E. Luevano-Hipolito; Mayte G. Fabela-Cedillo; J. L. Aleman-Ramirez; Leticia M. Torres-Martínez; P. J. Sebastian (Energy, Ecology and Environment, 2025)
This work aims to propose earth-abundant materials for CO 2 photoreduction to generate renewable solar fuels to provide practical solutions to global warming. The selected material in this case is cuprous oxide (Cu 2 O), one of the most promising photocatalysts for CO 2 photoreduction due to its high affinity to solar radiation and electronic properties. Cu 2 O nanoparticles (NPs) were synthesized using Psidium guajava residue for the photocatalytic CO 2 reduction. The aqueous residue of the Psidium guajava fruit proved to be suitable for stabilizing and acting as a reducing agent for the synthesis of Cu 2 O NPs. The XRD analysis confirmed the formation of the cubic structure of Cu 2 O. The nanoparticles absorb light from 430 nm with a direct bandgap value of around 1.8 eV. Cu 2 O NPs exhibited activity for CO 2 photoreduction, whose efficiency was optimized by an orthogonal Taguchi L 9 design. The factors studied were catalyst loading, air flow, and temperature. During the use of Cu 2 O NPs in the CO 2 photoreduction HCOOH was identified as the main product, with an optimized production of 103.4 µmol h − 1 under visible light. Also, it was demonstrated the photocatalytic activity of the Cu 2 O NPs for H 2 evolution by water splitting. Graphical Abstract

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

A geophysical assessment of the Termas de Río Valdez geothermal area (Tierra del Fuego, Argentina) - Jorge G. Lozano; Donaldo M. Bran; Sebastian Ramirez; Florencia B. Restelli; Stefania Bunicontro; Federico Esteban; Marco Menichetti; Emanuele Lodolo; Alberto Renzulli; Juan F. Vilas; Alejandro Tassone (Geothermics, 2024)

Fine-scale time series surveys reveal new insights into spatio-temporal trends in coral cover (2002–2018), of a coral reef on the Southern Great Barrier Reef - Chris Roelfsema; Eva M. Kovacs; Julie Vercelloni; Kathryn Markey; Alberto Rodriguez-Ramirez; Sebastian Lopez-Marcano; Manuel Gonzalez-Rivero; Ove Hoegh-Guldberg; Stuart R. Phinn (Coral Reefs, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Coral Reef Community Changes in Karimunjawa National Park, Indonesia: Assessing the Efficacy of Management in the Face of Local and Global Stressors - Emma V Kennedy; Julie Vercelloni; Benjamin P Neal; Ambariyanto; Dominic E.P. Bryant; Anjani Ganase; Patrick Gartrell; Kristen Brown; Catherine J.S. Kim; Mu’alimah Hudatwi; Abdul Hadi; Agus Prabowo; et al. (Journal of Marine Science and Engineering, 2020)
Karimunjawa National Park is one of Indonesia’s oldest established marine parks. Coral reefs across the park are being impacted by fishing, tourism and declining water quality (local stressors), as well as climate change (global pressures). In this study, we apply a multivariate statistical model to detailed benthic ecological datasets collected across Karimunjawa’s coral reefs, to explore drivers of community change at the park level. Eighteen sites were surveyed in 2014 and 2018, before and after the 2016 global mass coral bleaching event. Analyses revealed that average coral cover declined slightly from 29.2 ± 0.12% (Standard Deviation, SD) to 26.3 ± 0.10% SD, with bleaching driving declines in most corals. Management zone was unrelated to coral decline, but shifts from massive morphologies toward more complex foliose and branching corals were apparent across all zones, reflecting a park-wide reduction in damaging fishing practises. A doubling of sponges and associated declines in massive corals could not be related to bleaching, suggesting another driver, likely declining water quality associated with tourism and mariculture. Further investigation of this potentially emerging threat is needed. Monitoring and management of water quality across Karimunjawa may be critical to improving resilience of reef communities to future coral bleaching.

Draft whole genome sequence of the cyanide‐degrading bacterium P seudomonas pseudoalcaligenes CECT 5344 - Víctor M. Luque‐Almagro; Felipe Acera; Ma Isabel Igeño; Daniel Wibberg; Ma Dolores Roldán; Lara P. Sáez; Magdalena Hennig; Alberto Quesada; Ma José Huertas; Jochen Blom; Faustino Merchán; Ma Paz Escribano; et al. (Environmental Microbiology, 2013)
Summary P seudomonas pseudoalcaligenes CECT 5344 is a Gram‐negative bacterium able to tolerate cyanide and to use it as the sole nitrogen source. We report here the first draft of the whole genome sequence of a P . pseudoalcaligenes strain that assimilates cyanide. Three aspects are specially emphasized in this manuscript. First, some generalities of the genome are shown and discussed in the context of other P seudomonadaceae genomes, including genome size, G + C content, core genome and singletons among other features. Second, the genome is analysed in the context of cyanide metabolism, describing genes probably involved in cyanide assimilation, like those encoding nitrilases, and genes related to cyanide resistance, like the cio genes encoding the cyanide insensitive oxidases. Finally, the presence of genes probably involved in other processes with a great biotechnological potential like production of bioplastics and biodegradation of pollutants also is discussed.